DIVERSIFIKASI PRODUK AGROWISATA JAMBU BIJI MERAH PUJA JANTI REJO NGARGOYOSO KARANGANYAR - Hidup Marsudi; Jaelani Jaelani; Kasidin Kasidin; Totok Susilo Pamuji Nugroho (STIE Atma Bhakti, 2022)
ABSTRACTThe purpose of this community service activity is to introduce business development through product diversification by utilizing existing materials as an alternative to developing the target business of the guava farmer group in Jantirejo Village, Kec. Ngargoyoso Central Java expected benefits from this community service Farmers can get to know how to diversify products by utilizing materials and natural resources as a way to increase the business income of red guava farmer groups in Jantirejo Village, Kec. Ngargoyoso Central Java. This community service is carried out at the head of the Business group having its address at Candi, RT.02/RW.04, Jatirejo, Kec. Ngargoyoso, Karanganyar Regency, Central Java. The activity was carried out starting from the first visit to talk with the head of the business group, Mr. M. Mandatory as a business pioneer, followed by a field survey and identifying problems faced by the red guava farmer group Innovation that can meet the needs and tastes of consumers is absolutely necessary if business people do not want to lose their customers and grow the demand for their products. Maintaining and even growing new demand is certainly not an easy matter for business people. Diversification is the expansion or addition of goods or services to increase the company's profitability guava agricultural product diversification a. Guava plantations 1) Guava fruit 2) Guava seeds b.. Processed products 1) Guava ice cream 2) Red guava syrup 3) Guava chips 4) Guava leaf chips 5) Guava juice c. Tourism Products 1) Picking guava 2) Breding guavaKeywords : Innovation, Diversification, Farming, Guava ABSTRAKSI Tujuan dari kegiatan pengabdian masyarakat ini adalah mengenalkan pengembangan usaha melalui diversifikasi produk dengan memanfaatkan bahan-bahan yang sudah ada sebagai salah satu alternatif untuk mengembangankan usaha sasaran kelompok usaha petani jambu merah di Desa Jantirejo , Kec. Ngargoyoso Jawa Tengah. Manfaat yang diharapkan dari pengabdian masyarakat ini adalah petani dapat mengenal bagaimana melakukan diversifikasi produk dengan memanfaatkan bahan bahan dan sumberdaya alam sebagai salah satu cara untuk meningkatkan pendapatan usaha kelompok usaha petani Jambu biji merah di Desa Jantirejo , Kec. Ngargoyoso Jawa Tengah Pengabdian masyarakat ini dilaksanakan tempat ketua kelompok Usaha yang beralamat di Candi, RT.02/RW.04, Jatirejo, Kec. Ngargoyoso, Kabupaten Karanganyar Jawa Tengah. Kegiatan dilakukan dimulai dari kunjungan pertama bincang-bincang dengan ketua kelompok usaha Bapak M. Wajib selaku perintis usaha dilanjutkan dengan survey lapangan dan mengidentivikasi masalah yang dihadapi kelompok usaha petani jambu biji merah. Diversifikasi adalah perluasan atau penambahan barang atau jasa untuk meningkatkan profitabilitas perusahaan. Diversifikasi produk pertanian jambu a. Perkebunan Jambu 1) Buah jambu 2) Bibit jambu b.. Produk Olahan 1)Eskrim jambu 2) Sirup jambu merah 3)Kripik jambu 4)Kripik daun jambu 5) Jus jambu c. Produk Wisata 1) Petik jambu 2)Breding jambu Kata kunci : Inovasi, Diversivikasi, Usaha tani, Jambu